The COVID-19 pandemic altered the modality, but not the frequency, of formal cognitive assessment. Issue 21 (9th October 2022) - Webb, Sam S.; Kontou, Eirini; Demeyere, Nele
Abstract: Purpose: We investigated the impacts of the COVID-19 pandemic on the modality of formal cognitive assessments (in-person versus remote assessments). Materials and methods: We created a web-based survey with 34 items and collected data from 114 respondents from a range of health care professions and settings. We established the proportion of cognitive assessments which were face-to-face or via video or telephone conferencing, both pre- and post-March 2020. Further, we asked respondents about the assessment tools used and perceived barriers, challenges, and facilitators for the remote assessment of cognition. In addition, we asked questions specifically about the use of the Oxford Cognitive Screen. Results: We found that the frequency of assessing cognition was stable compared to pre-pandemic levels. Use of telephone and video conferencing cognitive assessments increased by 10% and 18% respectively. Remote assessment increased accessibility to participants and safety but made observing the subtleties of behaviour during test administration difficult. The respondents called for an increase in the availability of standardised, validated, and normed assessments. Conclusions: We conclude that the pandemic has not been detrimental to the frequency of cognitive assessments. In addition, a shift in clinical practice to include remote cognitive assessments is clear and wider availability of validated and standardised remote assessments is necessary. IMPLICATIONS FOR REHABILITATION: We caution the wider use and interpretation of remote formal cognitive assessments due to lack of validated, standardised, and normed assessments in a remote format. Clinicians should seek out the latest validation and normative data papers to ensure they are using the most up to date tests and respective cut offs. Support is needed for individuals who lack knowledge/have anxiety over the use of technology in formal cognitive assessments